2014
DOI: 10.4172/2332-0877.1000152
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Activities and Schistosomiasis Infection in the Kassena-Nankana District of Northern Ghana

Abstract: Schistosomiasis is a common cause of morbidity especially among rural children in less developed countries. The extent and distribution of schistosomiasis infection among school-age children was assessed and the association between some childhood activities and prevalence of infection was determined in northern Ghana. A cross-sectional study was conducted during which stool and urine samples were collected from children 6-15 years. Samples were analysed using the Kato-Katz technique and the 10 ml urine filtrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
2
1
0
Order By: Relevance
“…These findings are similar to those found by several authors, especially in Mali [20], in Kenya [25], in Ethiopia [26], and in Democratic Republic of the Congo [21]. However, the results differ from several studies where male predominance was reported in Yemen [24], in Ethiopia [27], and in Ghana [28]. …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are similar to those found by several authors, especially in Mali [20], in Kenya [25], in Ethiopia [26], and in Democratic Republic of the Congo [21]. However, the results differ from several studies where male predominance was reported in Yemen [24], in Ethiopia [27], and in Ghana [28]. …”
Section: Discussionsupporting
confidence: 90%
“…The findings showed that schistosomiasis was significantly associated with practices of swimming/bathing in open water ( p < 0.001); these results are similar to those found in Ghana [28], Nigeria [18], and Ethiopia [29]. …”
Section: Discussionsupporting
confidence: 77%
“…Although pupils and students had the highest prevalence (36.7%) and mean egg load (40 eggs/10 mL), there was however no significant difference in prevalence (V = 0.076, P = .56) and egg load (H=4.407, P=.319) between participants of different occupations. It is possible that the necessity for water used to prepare for school and household chores may cause this group of individuals to be in greater contact with water on a daily basis [20]. This group of children is known to spend time on recreational activities such as swimming which exposes them to infection by cercariae [1].…”
Section: Risk Factors Of Urinary Schistosomiasismentioning
confidence: 99%
“…Human schistosomiasis, though less fatal, but debilitating and chronic in nature, is among a set of 17 neglected tropical infectious diseases of poverty that is currently posing a threat to the wellbeing of 2 billion people in the world [ 1 ]. The aetiological agent of urogenital schistosomiasis is the infective stage (cercaria) of Schistosoma haematobium , a digenetic trematode plathyhelminth whose intermediate hosts are some species of gastropod snails in the genus Bulinus [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%